Analytical Method Development and Validation for Simultaneous Estimation of Nebivolol and Valsartan in Tablet Dosage Form by RP-HPLC - K. Veditha (Journal of Global Pharma Technology, 2018)
A rapid, sensitive, simple and precise reverse-phase high-performance liquid chromatographic (RP-HPLC) method for the simultaneous estimation of nebivolol and valsartan in tablet dosage forms has been developed. The compounds were well separated on Waters HPLC 2965 system using Alltima C18 column (150 mmX4.6 mm, dp=5 mm) and PDA detector with mobile phase consisting of buffer containing 3.3pH Potassium di hydrogen phosphate: acetonitrile: methanol in the ratio 45:35:20 at a flow rate of 1.0 mL/min with injection volume at 20ml and wavelength monitered at 280 nm, The Rt for Nebivolol & Valsartan were found to be 2.463& 4.017mins, respectively. Validation of the proposed method was carried out according to International Conference on Harmonisation (ICH) guidelines. Linearity range was obtained for NB and VT over the concentration range of 2.5-15 and 40-240mg/mL and the r2 values were 0.999 for both drugs. The calculated %RSD and recoveries of the Nebivolol and Valsartan were 0.62, 0.63 and 100.54%, 101.02% correspondingly. The calculated LOD and LOQ values were 0.09ppm, 0.31ppm and 0.28ppm, 0.95ppm correspondingly. Thus the present study showed that the developed RP-HPLC method is sensitive and selective for estimation of Nebivolol and Valsartan in combined dosage form.Keywords: Nebivolol, Valsartan, RP-HPLC, ICH guidelines.